Fade to black!. Issue 4 (December 2020) - Yousaf, Zohaib; Jamshaid, Muhammad Bilal; Khan, Dawlat; Murshed, Khaled A.; Munir, Huma
A 71-year-old man presented to the emergency room with chest pain, dry cough, shortness of breath and night sweats for 10 days. He had no fever, flu-like symptoms, sputum production or haemoptysis. There was no history of recent travel or sick contacts. A general review of systems was remarkable for subjective weight loss and malaise. He was an active smoker with a 100 pack-years smoking history and a past medical history of rectal squamous cell carcinoma (SCC). His cancer was treated with chemoradiotherapy and had been in remission for 8 years before the presentation. He was also known to have COPD, Global Initiative for Chronic Obstructive Lung Disease (GOLD) category B, well-controlled, with no recent hospitalisations or exacerbations over the past year. Black pleural effusion is a rare entity and may be a diagnostic dilemma. This interactive case discusses the various steps involved to reach the diagnosis. https://bit.ly/3dFJPTS